1999
DOI: 10.1093/gerona/54.8.m423
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Physician Recommendations To Exercise Among Older Adults

Abstract: Although physician advice appeared to be targeted to subgroups that could benefit, physician advice on exercise could be particularly increased for patients over 75 years of age, those currently not thinking about an increase in physical activity, and those currently active patients who may benefit from ongoing physician advice to promote maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 24 publications
3
34
1
Order By: Relevance
“…Physicians' offering of general medical advice is affected by several factors, including the patient's age, sex, race, educational level, insurance status, income, perceived health status, health behaviors, and geographic location. [41][42][43][44][45] Studies have shown that those who get advice from health care providers are more likely to make lifestyle changes than those who do not get this advice. 32 Simple verbal advice or pamphlets from a physician resulted in increased rates of physical activity in a comparison with usual care.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians' offering of general medical advice is affected by several factors, including the patient's age, sex, race, educational level, insurance status, income, perceived health status, health behaviors, and geographic location. [41][42][43][44][45] Studies have shown that those who get advice from health care providers are more likely to make lifestyle changes than those who do not get this advice. 32 Simple verbal advice or pamphlets from a physician resulted in increased rates of physical activity in a comparison with usual care.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys indicate that relatively few healthcare providers deliver such messages on a regular basis. 85 Where relevant, it may be useful to build greater physical activity expertise and capacity among public health practice groups, as well as develop methods for enhancing cross-disciplinary competencies and partnerships with planning, land use, and transportation experts. Harnessing the energy, resources, expertise, and advocacy skills of non-profit and nongovernmental organizations is also indicated.…”
Section: Practicementioning
confidence: 99%
“…[25][26][27][28] Despite the recent appeals for more physical activity counseling in clinical care and the fact that most individuals with diabetes have at least some contact with a primary care provider, little to no increase in counseling was observed over the past few decades.…”
Section: Literature Review Conclusionmentioning
confidence: 99%